Solanum dulcamara's response to eggs of an insect herbivore comprises ovicidal hydrogen peroxide production. (21st September 2017) - Geuss, Daniel; Stelzer, Sandra; Lortzing, Tobias; Steppuhn, Anke
Abstract: Plants can respond to insect oviposition, but little is known about which responses directly target the insect eggs and how. Here, we reveal a mechanism by which the bittersweet nightshade Solanum dulcamara kills the eggs of a generalist noctuid herbivore. The plant responded at the site of oviposition by Spodoptera exigua with formation of neoplasms and chlorotic tissue, accumulation of reactive oxygen species and induction of defence genes and proteins. Transcriptome analysis revealed that these responses were reflected in the transcriptional reprogramming of the egg‐laden leaf. The plant‐mediated egg mortality on S. dulcamara was not present on a genotype lacking chlorotic leaf tissue at the oviposition sites on which the eggs are exposed to less hydrogen peroxide. As exposure to hydrogen peroxide increased egg mortality, while catalase supplementation prevented the plants from killing the eggs, our results suggest that reactive oxygen species formation directly acts as an ovicidal plant response of S. dulcamara . Abstract : While plant defences to tissue feeding life stages of insect herbivores are well investigated, much less is known on plant defence responses to insect oviposition. This study unveils a simple and effective plant defence mechanism against insect eggs that is based on ovicidal hydrogen peroxide production. Until now, the role of such reactive oxygen species during plant responses to insects is merely viewed in their function as signalling components. Yet, Solanum dulcamara 's ovicidal hydrogen peroxide production suggests broader functions for the release of reactive oxygen species in ecological interactions.